Family Return Migration - Till Nikolka (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This paper investigates the role of family ties for international return migration decisions. The presence of children in the household affects return propensities of couples in different ways. Results suggest that schooling considerations as well as factors related to cultural identity play a role for family return migration. Moreover, the paper studies self-selection into return migration with respect to the partners' incomes. Couples returning from Denmark to the non-Nordic countries are positively selected with respect to primary earner income. Positive selection holds for male and female primary earners; it is weaker among dual earner couples and among couples with children.
Keywords: F22; J13; J61; 330; International migration; Family migration; Return migration; Education